Characterizing the Cellular Role of PHF6 - Todd, Matthew Andrew Melville (Université d'Ottawa / University of Ottawa, 2015)
Defective chromatin remodeling proteins are associated with both germline and acquired human disease. PHF6 is encoded by an X-linked gene that is predominantly expressed in the brain and thymus. Structurally, PHF6 contains nuclear and nucleolar localization sequences as well as two ZaP domains, which bind dsDNA. Germline mutations in PHF6 are the cause of BFLS, an XLID, while somatic PHF6 mutations have been identified in T-ALL, AML, and CML. Indeed, screening of a pediatric cohort of nine T-ALL patients revealed a novel H329Q mutation. In a further clinical analysis, T-ALL onset occurred in a 9-year old male BFLS patient with an R342X mutation, suggesting that BFLS might be a cancer predisposition syndrome. To better understand its protein function, recombinant PHF6 was co-immunoprecipitated for a mass spectrometry based proteomic screen. Notably, PHF6 co-purified with multiple constituents of the NuRD complex, an important transcriptional regulator during embryogenesis and lineage commitment with particularly well characterized responsibilities during lymphogenesis. PHF6-NuRD localization was restricted to the nucleoplasm, however PHF6 also co-purified with several ribosomal and splicing proteins. When examined further, PHF6 was found to be recruited to the nucleolus by an RNA-mediated interaction and co-localized within the subnucleolar FC and DFC compartments. ChIP-qPCR revealed that PHF6 binds to transcribed regions of rDNA, resulting in the repression of rRNA. These data thus present a model of PHF6 acting as a tumour suppressor by mediating both nucleoplasmic and nucleolar transcriptional events.
Keywords: PHF6; BFLS; T-ALL; AML; Nucleolus; NuRD; rDNA